2011
DOI: 10.1007/s10900-011-9410-6
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Self-Efficacy and Hypertension Self-Care Activities Among African American Adults

Abstract: Chronic disease management requires the individual to perform varying forms of self-care behaviors. Self-efficacy, a widely used psychosocial concept, is associated with the ability to manage chronic disease. In this study, we examine the association between self-efficacy to manage hypertension and six clinically prescribed hypertension self-care behaviors. We interviewed 190 African Americans with hypertension who resided in the greater metropolitan Charlotte area about their self-efficacy and their hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
152
5
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(190 citation statements)
references
References 40 publications
16
152
5
17
Order By: Relevance
“…Rakwell suggests that patients with higher level of education have better decision-making powers to adopt health behaviors [20]. Some studies state that some people with low level of education do not understand the instructions correctly and this leads to a lack of self-efficacy in the adoption of these behaviors [27]. In the analysis of other factors, there was a significant relationship between marital status and self-regulation behaviors so that the average self-regulation performance of married individuals was better compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Rakwell suggests that patients with higher level of education have better decision-making powers to adopt health behaviors [20]. Some studies state that some people with low level of education do not understand the instructions correctly and this leads to a lack of self-efficacy in the adoption of these behaviors [27]. In the analysis of other factors, there was a significant relationship between marital status and self-regulation behaviors so that the average self-regulation performance of married individuals was better compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…High selfefficacy is important in achieving chronic disease control, and has been found to predict more successful hypertension self-management in African Americans. 29,30 Behavioral research provides some clues why well-meaning attempts to educate patients or provide them feedback may backfire (see Fig. 1).…”
Section: Shortcomings Of Current Strategies To Control Chronic Diseasesmentioning
confidence: 99%
“…We proposed that control beliefs may be relevant in this population, based on previous work showing that condition or task-specific control beliefs were associated with health behaviors and physiologic markers. 8,9,[21][22][23][24] Some evidence also indicated general control beliefs were associated with differences in illness-specific control beliefs. 37 It is possible that we did not detect interaction effects because general control beliefs have diverse effects on health, beyond self-care behaviors solely associated with DM and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…studies of those with DM and hypertension indicated that control beliefs may impact clinical outcomes and behavioral change, but only short-term outcomes were evaluated (e.g., dietary adherence, blood pressure and glycemic control). 8,9,[21][22][23][24] We found no investigations addressing the impact of control beliefs on the long-term risk for major cardiovascular events and mortality in DM and hypertension.…”
Section: Introductionmentioning
confidence: 97%